Where contrast agent concentration really matters: a comparison of CT and MRI - Heiland, Sabine; Erb, Gunter; Ziegler, Simon; Krix, Martin (Investigative radiology, 2010)
Objectives: - First pass contrast-enhanced magnetic resonance imaging (MRI) and computed tomography (CT) are influenced by parameters that characterize the injected bolus. The aim of this study was to assess the role of contrast agent concentration and the differences between MRI and CT. - Material and Methods: - We systematically evaluated the published literature to define the differences between MRI and CT with regards to the influence of contrast agent concentration and flow rate on signal enhancement and image quality. Subsequently, we used a simulation model to simulate bolus dispersion in the human body for contrast agents with different concentration. We performed this simulation for different injection times (3-25 seconds) as well as for single and double contrast agent dose, and calculated the effect of contrast agent concentration and dose on the increase of local contrast agent concentration. - Results: - Although CT studies have shown that even a moderate increase in contrast agent concentration leads to higher peak concentration in the tissue or artery of interest, MRI studies have failed to show a marked benefit of higher concentration. The simulation demonstrated that the use of high concentrated contrast agent leads to an increase in local contrast agent concentration within the tissue or artery of interest, only if injection time is long (in CT commonly >10 seconds) compared with the time constant of bolus dispersion (about 5 seconds in humans). If the injection time is shorter (in MRI commonly 1-4 seconds), the local contrast agent concentration is mainly affected by the injected dose. - Conclusion: - Contrast agent concentration is a key parameter for the optimization of dynamic imaging techniques such as angiography or perfusion in CT, whereas in dynamic MRI, contrast agent dose and relaxivities are the leading parameters.
Gesehen am 11.04.2023